ADDRESSING SOIL HEALTH MANAGEMENT ISSUES IN INDIA - Patel, Amrit (International Journal of Research -GRANTHAALAYAH, 2016)
World has been observing 5th December since 2012 as the World Soil Day to ensure maintenance of soil health, This was complimented by the United Nations’ General Assembly declaring 2015, as the International Year of Soils to create awareness among all stakeholders and promote more sustainable use of soil being the critical resource. On this occasion, UN Secretary General, Ban Ki-moon had said that without healthy soils life on Earth would be unsustainable. Indeed, soils are the foundation of agriculture. He had urged all Governments to pledge to do more to protect this important yet forgotten resource. A healthy life is not possible without healthy soils. According to the Director General of the FAO, Jose Graziano da Silva, today, world has more than 805 million people facing hunger and malnutrition. Soils are under increased pressure because population growth will require an approximately increase of 60 per cent in food output and competing land uses.Unfortunately, 33 per cent of our global soil resources are under degradation and human pressures on soils are reaching critical limits, reducing and sometimes eliminating essential soil functions. He had emphasised the role of all stakeholders in promoting the cause of soils as it is important for paving the road towards a real sustainable development for all and by all. Against this background, this article briefly highlights the significance and aspects of soil health management in India and suggests aspects of strategic action plan to conserve this precious resource for the benefit of mankind.